Effect of carbon on the properties of CrN coatings formed by cathodic arc evaporation in stationary system - Kuprin, A.S.; Kolodiy, I.V.; Ovcharenko, V.D.; Tolmachova, G.N.; Gilewicz, A.; Lupicka, O.; Warcholinski, B. (Вопросы атомной науки и техники, 2016)
Due to good resistance to oxidation and wear chromium nitride coatings are widely used in industry. The works aimed at further improving, for example by carbon doping, the properties of the coatings. The goal of this study was to assess effect of carbon addition to CrN coatings deposited without substrates rotation on the deposition rate, roughness, structure, hardness, adhesion, wear and comparison with properties of CrN coating.